Facilitating flow experience in people with intellectual disability using a music intervention program - Soltani, Amanallah; Roslan, Samsilah; Abdullah, Maria Chong; Chan, Cheong Jan (Canadian Center of Science and Education, 2011)
Flow is an internal state defined as a condition whereby a person is intensively involved in an activity and ignores the time spent and the place that he/she is in. The purpose of this paper is to empirically support strategies that are assumed to facilitate flow experiences among people with intellectual disability using a music intervention program. For this purpose, thirty adolescents and young adults with mild to moderate intellectual disability were randomly selected to participate in a within subject experimental design with four conditions. The results of one way repeated measure ANOVA and its following comparisons in pairs revealed that the participants were unable to sustain flow experience when no optimal challenge was provided for them. However, providing successful optimally challenging musical experiences for these people or stimulating them to look for new challenges by involving them in innovative behaviors are effective strategies to facilitate their flow experiences.